Content of the concept of blackmail in the legal sphere and ordinary consciousness (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
The author of the article determines that in the legal field, blackmail is recognized because of the qualification sign of a threat; in linguistic sources – as intimidation, demand, extortion, coercion, insistence, racketeering, constraint. The author explains that the narrower legal meaning of the term has created the basis for a fuller understanding of the phenomenon of intimidation by the threat of disclosure.The author notes that at the level of ordinary consciousness, blackmail has an explanation that is significantly different from what is in the legislative sphere. It is perceived as any verbal action against another person with coercive. Non-criminal blackmail can be embodied by direct means of exposure or based on covert manipulative actions. The blackmailer's communicative behaviour makes it possible to talk about destructive communication. This process allows directive tactical-situational promptings with a request, an order, a persistent request, an instruction, a directive, a ban; aggressive language acts, exclusive lexical content, structuring of expressions with certain syntactic unities, a system of stylistic means and techniques.The article describes an experiment that made it possible to conclude: only 20% of respondents interpret the concept, using its narrow legal content, 80% perceive the meaning of blackmail through a set of their own sensual and mental images that appear being based on their nomination experience of illegal effects. Such results testify to the process of determinologization, understanding of the concept as a common phenomenon, which is a kind of psycho-emotional influence of one person on another in order to obtain any personal benefit.
Keywords: the concept of blackmail; communicative tactics; determinologization; legislative norms; ordinary consciousness